After-Images of the City - Ingenschay, Dieter; Resina, Joan Ramon (Book collections on Project MUSE., 2003)
Criticism on the textual and iconographic construction of the city is extensive, yet the problem of historical change in representations of "the urban" has received little attention. Believing traditional accounts are limited by their reflection of a specific historical moment, Joan Ramon Resina and Dieter Ingenschay focus, by contrast, on transition. In essays written for this volume, scholars of literary and visual studies, the history of architecture, cultural theory, and urban geography explore the ways perceptual or conceptual paradigms of the city supersede or replace others, while at the same time retaining the "after-image" of what went before. The writers touch on a wide variety of issues related to contemporary urban cultures as they journey through cities including New York, Barcelona, Madrid, Paris, Tijuana, Berlin, and London. Drawing on the work of Roland Barthes, Walter Benjamin, Camilo Jose Cela, Honore de Balzac, and Alfred Stieglitz, their approach is broadly cultural rather than technical. After-Images of the City takes into account the intrinsic instability of the image and reveals that representations of the modern metropolis cannot be fixed in time and history